2002
DOI: 10.1097/00006324-200207000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Further Assessment of Gender- and Blink Pattern-Related Differences in the Spontaneous Eyeblink Activity in Primary Gaze in Young Adult Humans

Abstract: Different patterns of spontaneous eyeblink activity can result in differences in the SEBR and IEBI values. It is proposed that the pattern of spontaneous eyeblink activity where there are similar intervals between each eyeblink event should be referred to as a "normal" (rather than symmetrical) pattern and should be considered as the normal eyeblink activity, both from a physiological and statistical perspective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
94
3
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(111 citation statements)
references
References 20 publications
12
94
3
2
Order By: Relevance
“…The present sample did contain more female than male infants with faster rates of SB. However, previous work with infants has not shown sex differences in resting SB rate (Bacher & Smotherman, 2004a;Zametkin, Stevens, & Pittman, 1979), but some studies of adults have found task-related sex differences in SB (Bentivoglio et al, 1997;Doughty, 2002).…”
Section: Discussionmentioning
confidence: 90%
“…The present sample did contain more female than male infants with faster rates of SB. However, previous work with infants has not shown sex differences in resting SB rate (Bacher & Smotherman, 2004a;Zametkin, Stevens, & Pittman, 1979), but some studies of adults have found task-related sex differences in SB (Bentivoglio et al, 1997;Doughty, 2002).…”
Section: Discussionmentioning
confidence: 90%
“…Controversial evidence exists in the literature about blink parameter differences between males and females, [24][25][26] with some authors describing a possible link between SEBR sex differences and hormone-related factors such as use of estroprogestinics or phase of the ovarian cycle, both of which may affect blinking on the one hand and tear production on the other. The present findings give support to the existence of sex differences, although further research with two groups of OSDI-matched males and females is required to investigate whether these differences have an ocular surface or central origin.…”
Section: Discussionmentioning
confidence: 99%
“…Results were compared with those obtained while subjects were observing in silence a landscape picture on the median plane at 2 m. In addition, given the documented-albeit still controversial-influence of age and sex on SEBR, which some authors have associated with the higher prevalence of dry eye in the elderly population and in females, [22][23][24][25][26] the relationship between these predictor variables and blink parameters was investigated.…”
mentioning
confidence: 99%
“…In the above table, increases in SEBR are observed from reading (lowest) through normal gaze to conversation (highest) that would correlate broadly with expected physical behaviour of the eye for each activity. In addition, Doughty [33] distinguishes inter-eyeblink interval (IEBI) between normal (regular interval between blinks), I-type (random) and J-Type (mainly short with occasional longer intervals) and provides suggested values for all quantities ( Table 2 shows, a broad inverse correlation exists between SEBR and IEBI (as would be expected). Although Doughty indicates no absolute values can be taken from this study, a broad indication of SEBR increase depending on task (reading/gazing/conversation) and inverse variation between SEBR and IEBI depending on interval type (I-type/Jtype/normal) can be made.…”
Section: Eyeblinksmentioning
confidence: 95%